2015
DOI: 10.1111/jir.12249
|View full text |Cite
|
Sign up to set email alerts
|

Towards a framework in interaction training for staff working with clients with intellectual disabilities and challenging behaviour

Abstract: In conducting a functional analysis of staff interpersonal behaviour, the results of this study can be used both as a framework in staff-client interaction training and in clinical practice for treating challenging behaviour. The emphasis in training and practice should not only be on the bidirectional dynamics of control and affiliation between staff and clients, but also - in order of importance - on the impact of staff emotions, self-efficacy, self-reflection and insight, coping style, team climate and attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 62 publications
3
52
0
Order By: Relevance
“…As aggression towards staff by patients in forensic settings is common (Broderick, Azizian, Kornbluh, & Warburton, ; Freestone et al, ; Nicholls, Brink, Greaves, Lussier, & Verdun‐Jones, ), these findings suggest that emotion regulation may influence the way in which staff working with patients with a diagnosis of personality disorder in forensic settings cope with the challenging behaviour of their patients. In the study by Willems et al (), emotion regulation was missing, and possibly therefore, no relation was found between task‐focused coping style and interpersonal staff behaviour, while the results for avoidance‐focused coping style were ambiguous. We expect that the task‐focused or avoidance‐focused coping skills of staff will only improve their behaviour towards patients if they adequately regulate their emotions by reappraising the situation and by refraining from suppressing their emotions.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…As aggression towards staff by patients in forensic settings is common (Broderick, Azizian, Kornbluh, & Warburton, ; Freestone et al, ; Nicholls, Brink, Greaves, Lussier, & Verdun‐Jones, ), these findings suggest that emotion regulation may influence the way in which staff working with patients with a diagnosis of personality disorder in forensic settings cope with the challenging behaviour of their patients. In the study by Willems et al (), emotion regulation was missing, and possibly therefore, no relation was found between task‐focused coping style and interpersonal staff behaviour, while the results for avoidance‐focused coping style were ambiguous. We expect that the task‐focused or avoidance‐focused coping skills of staff will only improve their behaviour towards patients if they adequately regulate their emotions by reappraising the situation and by refraining from suppressing their emotions.…”
Section: Introductionmentioning
confidence: 96%
“…In a related field of clients with intellectual disabilities and challenging behaviour, Willems, Embregts and colleagues (Willems, Embregts, Stams, & Moonen, ; Willems, Embregts, Hendriks, & Bosman, ; et al, 2014; Willems, Embregts, Hendriks, & Bosman, ) used Leary's interpersonal circumplex model (Leary, ) in research on which factors influence the interaction between staff and clients. Therefore, the results of research on the interaction between staff and clients with intellectual disabilities and challenging behaviour may be relevant to staff working with patients with a diagnosis of personality disorder in forensic settings.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations